Evaluation of osmoregulation and morpho-physiological responses of Borago officinalis under drought and salinity stress with equal osmotic potential. (February 2023) - Rostampour, Parvin; Hamidian, Mohammad; Movahhedi Dehnavi, Mohsen; Saeidimajd, Ghodrat Allah
Abstract: As the global demand for medicinal plants increases and the forthcoming climate change reveals itself, understanding the morpho-physiological behaviors of borage plants under salinity and drought stress can be significant. However, accurate comparison of these behaviors at different salinity and drought stress conditions requires a new approach to equalization at stress levels. This experiment was conducted in a greenhouse to identify the borage response to salinity (NaCl) and drought (PEG) stress conditions with equal osmotic potential (−0.371 and −0.742 MPa) with a post-stress recovery period. In general, both types of stress conditions caused plant damage, antioxidant defense, and increased osmolyte levels; however, the negative effect of drought stress on the growth and development of this plant was more than that of salinity stress. Borage had an acceptable capability to absorb and accumulate sodium in its leaves and considerably controlled the toxic effect of these ions on membrane destruction (malondialdehyde level) and potassium homeostasis and used the benefits of these ions for osmoregulation. In drought stress, the cause of significant damage to plant growth can be attributed to allocating a significant portion of plant energy to the synthesis of defense factors and osmo-protectants like proline. This damage delayed the reproductive growth and flowering of this plant and impaired the plant growth. The results of osmotic stress and the measurement of the growth potential of the plant in the recovery phase indicated that borage plant had better growth potential in salinity stress compared to dry stress by controlling the negative effect of salt ions, accumulating these ions in its organs, and allocating lower energy to osmoregulation. Graphical abstract: Image 1 Highlights: The salinity damage is not higher than those of drought stress in borage. Borage uses Na ions to regulate the osmotic potential under salinity stress. The energy allocation for the biosynthesis of organic osmolytes is costly. Osmotic adjustments by inorganic ions were more beneficial for borage. Drought stress led to a delay in the reproductive growth of borage.